2023
DOI: 10.2196/44197
|View full text |Cite
|
Sign up to set email alerts
|

The Success of Cancer Crowdfunding Campaigns: Project and Text Analysis

Abstract: Background Recent studies have analyzed the factors that contribute to variations in the success of crowdfunding campaigns for a specific cancer type; however, little is known about the influential factors among crowdfunding campaigns for multiple cancers. Objective The purpose of this study was to examine the relationship between project features and the success of cancer crowdfunding campaigns and to determine whether text features affect campaign suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Inability to work, disability from disease, and infectious complications suggest a debilitating and urgent condition, and reluctance to ask for help may portray a picture of resilience following the exhaustion of other means of fundraising, both of which may garner sympathy from potential donors. This finding on crowdsourcing for skin cancer following transplantation parallels the results from crowdsourcing for all cancers, where campaigns for high-mortality cancers that used emotional words to prompt empathy had raised more funds [9]. In another of our group's previous studies, where we analyzed factors associated with fundraiser success in GoFundMe campaigns raising money for plastic surgery conditions, we found that themes including inadequate insurance, travel costs, life-saving treatment, and end-of-life expenses were associated with a higher amount of funds raised (E Mark et al, unpublished data, May 2022).…”
Section: Principal Findingssupporting
confidence: 63%
“…Inability to work, disability from disease, and infectious complications suggest a debilitating and urgent condition, and reluctance to ask for help may portray a picture of resilience following the exhaustion of other means of fundraising, both of which may garner sympathy from potential donors. This finding on crowdsourcing for skin cancer following transplantation parallels the results from crowdsourcing for all cancers, where campaigns for high-mortality cancers that used emotional words to prompt empathy had raised more funds [9]. In another of our group's previous studies, where we analyzed factors associated with fundraiser success in GoFundMe campaigns raising money for plastic surgery conditions, we found that themes including inadequate insurance, travel costs, life-saving treatment, and end-of-life expenses were associated with a higher amount of funds raised (E Mark et al, unpublished data, May 2022).…”
Section: Principal Findingssupporting
confidence: 63%
“…O maior impacto sobre o interesse da população causado pelas campanhas sobre os cânceres de mama e próstata, comparados aos demais tipos de câncer, pode estar associado a uma maior incidência desses tipos de câncer nos países avaliados 2 , à existência de programas de rastreamento 10 , bem como ao grau de difusão e maturidade dessas campanhas, que contam com maiores investimentos de recursos financeiros, midiáticos e simbólicos para sua realização 42 . O laço rosa e o bigode, por exemplo, se tornaram ícones da luta contra o câncer de mama e próstata, ajudando a chamar a atenção, mobilizar e identificar as pessoas que apoiam essas causas 43 .…”
Section: Discussionunclassified
“…Much of the current literature has also focused on success factors as they relate to campaign outcomes (ie, how much money has been raised). Some of these factors include title and narrative length, younger age, gender (men), and early position in search results [ 13 , 14 ]. Understanding both campaign outcomes and the content of online talk on MCF pages is critical to describing campaigners’ financial coping experiences and identifying the utility of this financial coping behavior.…”
Section: Introductionmentioning
confidence: 99%